MAINTENANCE PROGRAMMING OF FLEXIBLE PAVEMENT BASED ON FUNCTIONAL CONDITIONS EVALUATION USING PAVEMENT CONDITION INDEX (PCI) METHOD AND BINA MARGA METHOD (CASE STUDY : JAKARTA-CIKAMPEK TOLL ROAD KM 16+000 TO 21+000) - Kumala Sari, Indah
Jakarta-Cikampek Toll Road is one of the toll roads managed by PT. Jasa Marga. One of the substances of services that must be provided by toll road operators in ensuring services for users who pay toll fee is the minimum condition of toll roads. Therefore, it is necessary to evaluate the functional pavement condition in advance to obtain an appropriate and sustainable maintenance program in adequate the substance. The methods of functional pavement condition evaluation that were commonly used are pavement condition index (PCI) method and Bina Marga method. This study evaluated the functional condition of pavement with PCI method and Bina Marga method, compared the evaluation results of the two methods, evaluated the damage type that most influenced maintenance cost needs based on deduct value and treatment recommendations for each type of damage, developed maintenance scenarios based on the evaluation of pavement condition results with PCI method and IRI value prediction based on simplified HDM-4 model, and chose maintenance scenarios with the minimum cost. The condition of pavement based on the evaluation results with PCI method is worse than the evaluation result with Bina Marga method. Some differences in evaluation results with both methods are caused by differences in the scale of the assessment, damage types and assessment indicators under review. Damage types that most affect maintenance costs are rutting at 45,54% and alligator cracking at 19,35%. The maintenance scenario with the minimum maintenance cost requirement is scenario 4, which is to perform reconstruction in the first year with accumulated maintenace costs is Rp144.335.974.113.